High-Definition 4K-3D Exoscope in Spine Surgery: A Single-Center Experience and Review of the Literature - Niccolò Innocenti; Nicoletta Corradino; Francesco Restelli; Vittoria Maria Luisa Cojazzi; Elio Mazzapicchi; Marco Schiariti; Vincenzo Levi; Francesco Costa (Medicina)
Background and Objectives: Binocular optical microscopy (OM) paved the way for a new era in brain and spine neurosurgery fields with the introduction of microsurgery. Despite its enormous contribution to modern neurosurgery, OM presents some intrinsic limitations that surgeons need to face during procedures such as prolonged non-ergonomic positions and decreased vision quality to the assistant eyepiece. To overcome these limitations, in recent years, new operative tools have been introduced, such as exoscopes. Here, we present our experience with exoscopes in spine surgery. Materials and Methods: In the period between January 2022 and December 2023, we gradually implemented the use of a high-definition 4K-3D exoscope (ORBEYETM, Olympus, Japan) in patients undergoing spinal surgery. Results: A total of 243 patients underwent spine surgery with exoscope magnification (47 intradural tumors, 99 lumbar degenerative cases, 79 cervical degenerative cases, 5 dorsal calcified disk herniations, 4 dural arteriovenous fistulas (dAVFs), and 9 others). We compared this cohort with a similar cohort of patients operated in the same period using OM based on different endpoints: operating time, complication rate, and infection rate. We did not find any statistically significant difference in any of the endpoints between these two groups. Conclusions: In our experience, the exoscope provides a better resolution of spinal anatomy and higher quality real-time images of the surgery for the entire OR team and improves the ergonomic posture of both surgeons, without lengthening the operating time and without increasing the rate of adverse events. Prospective studies with a larger cohort of patients are needed to further validate these findings.